MACHADO, Ida Lucia; MELLO, Renato de (orgs.). Análises do discurso hoje, volume 3. Rio de Janeiro: Nova Fronteira / Lucerna, 331 páginas, 2010. - Miranda, Cássio Eduardo Soares (Cadernos de Linguagem e Sociedade, 2011)
MACHADO, Ida Lucia; MELLO, Renato de (orgs.). Análises do discurso hoje, volume 3. Rio de Janeiro: Nova Fronteira / Lucerna, 331 páginas, 2010.